Security forecasts of terrorist attack - Blahova Marta (MATEC Web of Conferences, 2019)
This article deals with security developments in terrorism. In the introductory part, the article deals with the history and current situation of terrorism. Furthermore, the national ones are analyzed and International Security Strategy Papers on Counter-Terrorism. In the next part of this article, long-term safety forecasts from the Czech Republic are analyzed and foreign authors with a focus on terrorism. The main outcome of the article is a proposal for an alternative scenario of possible security developments in the area of terrorism within the European Union.